'The Michael Jordan of greatness'—Extracting Vossian antonomasia from two decades of The New York Times, 1987–2007. (28th January 2019) - Fischer, Frank; Jäschke, Robert
Abstract: Vossian antonomasia is a prolific stylistic device, in use since antiquity. It can compress the introduction or description of a person or another named entity into a terse, poignant formulation and can best be explained by an example: When Norwegian world champion Magnus Carlsen is described as 'the Mozart of chess', it is Vossian antonomasia we are dealing with. The pattern is simple: A source (Mozart) is used to describe a target (Magnus Carlsen), the transfer of meaning is reached via a modifier ('of chess'). This phenomenon has been discussed before (as 'metaphorical antonomasia' or, with special focus on the source object, as 'paragons'), but no corpus-based approach has been undertaken as yet to explore its breadth and variety. We are looking into a full-text newspaper corpus ( The New York Times, 1987–2007) and describe a new method for the automatic extraction of Vossian antonomasia based on Wikidata entities. Our analysis offers new insights into the occurrence of popular paragons and their distribution.